Racial animus and its association with punitive sentencing and crime types: Do Australian community attitudes reflect the United States'?. Issue 1 (March 2022) - Brookman, Ruth; Wiener, Karl; DeSoto, William; Tajalli, Hassan
The racial animus model argues that public support for punitive sentencing of criminal offenders is shaped by threat perceptions associated with cultural minority groups. This study applies the racial animus model to examine support for the punitive sentencing of criminal offenders in the United States and Australia. It also examines whether racial animus mediates the possible difference in punitive attitudes between each country toward different crime types. Online survey data were obtained in the US and Australia to assess racial animus and punitive attitudes using six different crime scenarios. Results indicate that (a) individuals with higher levels of racial animus demonstrate greater levels of punitiveness; (b) Australians have higher levels of racial animus as compared to their US counterparts; and (c) racial animus mediates the difference of punitive attitudes between the two countries. Overall, punitive attitudes and racial animus vary cross-culturally, with Australians demonstrating more racial animus. Our mediation model provides evidence for the importance of racial animus in the cross-cultural demand for the punishment of criminal offenders.